Pengaruh Zat Pengatur Tumbuh Organik terhadap Pertumbuhan Benih Tomat (Lycopersicum esculentum Mill.) yang Bersumber dari Hasil Panen Petani - Marlina Marlina (Savana Cendana, 2023)
The study aims to determine the effect of Growth Regulatory Substances (GRS) on the growth of tomato seeds of farmers' harvests. The research method used a completely randomized design non-factorial with three replications. The factors studied were Organic Growth Regulators consisting of bean sprout extract, onion extract and young coconut water with a concentration of 50% each. The variables observed were growth potential, germination rate, growth speed, growth synchronously, and seed vigor. The results showed that young coconut water with a concentration of 50% gave the best results at the rate of growth potential with a percentage of 95.83% and seed vigor with a percentage of 91.66%, while the best germination was found in onion extract with a percentage of 83.33%, while the best growth uniformity was found of bean sprout extract with a percentage of 75.00%. However, it can be concluded that organic PGR did not significantly affect the growth rate of tomato seeds.